What makes disaster donors different from non-donors. Issue 4 (29th July 2014) - Nogami, Tatsuya
Abstract : Purpose: – The purpose of this paper is to explore what would make disaster donors different from non-donors, with particular attention paid to differences in two forms of donations: the monetary donation that directly benefits the beneficiary and the charitable donation that is used by charitable organizations to support their disaster relief activities. Differences in the perceived effectiveness of other disaster relief activities, skepticism about charitable organizations, disaster experience, disaster preparedness, and disaster insight were also examined between the two groups. Design/methodology/approach: – A total of 300 Japanese participants were asked to complete a14-item questionnaire online. A series of comparative analyses were conducted to examine differences between donors and non-donors in the questionnaire items. Findings: – Although non-donors evaluated the effectiveness of the monetary donation more positively than the charitable donation, donors evaluated the effectiveness of all the disaster relief activities more positively than non-donors. Moreover, donors were more prepared for disasters and more insightful into the current situation of the disaster victims than non-donors. Research limitations/implications: – Along with the internal and external factors previously found, disaster awareness may be a key to increasing people's intention to donate for disaster victims. Such awareness could be fostered through successful disaster education and appropriate media coverage of disasters. Originality/value: – The findings that non-donors generally have a less positive view of disaster relief activities imply that non-donors may be less knowledgeable than donors about how charitable activities can work and benefit disaster victims.